The Duty of Memory: La Violencia between Remembrance and Forgetting (2017)
For most Colombians, April 9, 1948, stands as the most significant turning point in the twentieth century. Accordingly, the assassination of Liberal presidential candidate Jorge Eliecer Gaitan and the subsequent devastation of the country's capital by his followers triggered a spiral of violence that continues until today. April 9—often referred to as El Bogotazo—is therefore interpreted as a “seminal catastrophe” that divided the twentieth century into two halves. Whereas the years between the War of a Thousand Days (1899–1902) and the assassination of Gaitan are commonly associated with stability and peace, today's civil-war-like conditions are frequently seen as a direct consequence of the murder. In this perspective, the oftcited “crime of the century” is regarded as the starting point for political struggles that gradually evolved into the establishment of left- and rightwing armed groups (Schuster 52). In fact, leftist guerrillas like the Fuerzas Armadas Revolucionarias de Colombia (FARC; Revolutionary Armed Forces of Colombia), which despite recent peace talks still lead a bloody war against the state on the back of civil society, have their roots in the time of La Violencia. It is also true that the young Fidel Castro was wandering the streets of Bogota the very day of April 9, 1948, which some have taken as evidence of a “Communist conspiracy.” Following this theory, political violence was supposedly brought to Colombia from the “outside.” These and similar interpretations have in common the reduction of Colombia's complicated history of violence to individual actors and dualistic schemes. Depending on political affiliation, different actors are held responsible for the murder: the Conservatives, the Communists, the Central Intelligence Agency, and so on. Or was it, after all, the act of a lunatic? We do not know for sure. Since the alleged murderer Juan Roa Sierra probably suffered from delusions and was lynched immediately after the attack by an angry mob, El Bogotazo offers itself as projection screen for all kinds of conspiracy theories (Braun 263–72). Although none of these interpretations is outright wrong, they do not recount the whole story either. Thus, the two traditional parties—the Liberals and the Conservatives—politically exploited the figure of the liberal tribune just shortly after his murder. By manipulating historical facts, both tried to construct the myth of a popular martyr who would not belong to any specific political entity.